SORPTION OF YTTRIUM AND RARE EARTH ELEMENTS BY AMORPHOUS FERRIC HYDROXIDE: INFLUENCE OF SOLUTION COMPLEXATION WITH CARBONATE - Quinn K.A.; Byrne R.H.; Schijf J. (My University, 2006)
The influence of solution complexation on the sorption of yttrium and the rare earth elements (YREEs) by amorphous ferric hydroxide was investigated at 25 °C over a range of pH (4.0-7.1) and carbonate concentrations (0 M ? [CO32 -]T ? 150 ? M). Distribution coefficients, defined as i KFeT = [MSi]T / (MT ? [Si]), where [MSi]T is the total concentration of sorbed YREE, MT is the total YREE concentration in solution, and [Si] is the concentration of amorphous ferric hydroxide, initially increased in magnitude with increasing carbonate concentration, and then decreased. The initial increase of i KFeT is due to sorption of YREE carbonate complexes (MCO3+), in addition to sorption of free YREE ions (M3+). The subsequent decrease of i KFeT, which is more extensive for the heavy REEs, is due to the increasing intensity of YREE solution complexation by carbonate ions. The competition for YREEs between solution complexation and surface complexation was modeled via the equation:{Mathematical expression}where S?1 and S?2 are equilibrium constants for free YREE surface species, SCO3? 1 is the equilibrium constant for the YREE-carbonate surface species, SK1 is the surface protonation constant for amorphous ferric hydroxide, and HCO3 ?1, CO3H?1, and CO3H?2 are YREE solution complexation constants expressed in terms of bicarbonate concentrations. The equation, which includes (i) a single new constant (SCO3?1) for each YREE, (ii) previously published sorption coefficients (S?1 and S?2) determined in the absence of carbonate, and (iii) previously published solution complexation constants, precisely predicts both the absolute magnitude of i KFeT and the pattern of i KFeT values over our range of experimental conditions. Experimentally observed i KFeT values, spanning more than five orders of magnitude, are accurately described by our surface/solution complexation model. The log SCO3?1values determined for each YREE in this work are: Y(-1.30 ? 0.04), La(-0.39 ? 0.02), Ce(-0.21 ? 0.02), Pr(-0.22 ? 0.02), Nd(-0.20 ? 0.02), Sm(-0.20 ? 0.02), Eu(-0.26 ? 0.02), Gd(-0.38 ? 0.02), Tb(-0.40 ? 0.02), Dy(-0.51 ? 0.02), Ho(-0.57 ? 0.02), Er(-0.59 ? 0.02), Tm(-0.56 ? 0.02), Yb(-0.62 ? 0.02), and Lu(-0.59 ? 0.02).
Keywords: AMORPHOUS MEDIUM; CARBONATE; COMPLEXATION; RARE EARTH ELEMENT; SORPTION; YTTRIUM